2017
DOI: 10.1590/1807-1929/agriambi.v21n11p739-745
|View full text |Cite
|
Sign up to set email alerts
|

Saline water irrigation managements on growth of ornamental plants

Abstract: A B S T R A C TBiosaline agriculture is an option for using waters with lower quality. Thus, the objective of this study was to evaluate the growth of ornamental species under irrigation with increasing water salinity levels in two methods of water application. The study was conducted in a greenhouse, in the municipality of Fortaleza, Ceará, Brazil. The treatments were distributed in randomized blocks in split plots, with six levels of water salinity in the plots (0.6 -control, 1.2, 1.8, 2.4, 3.0 and 3.6 dS m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Yasemin (2020) [20] also presented that branch number and length of Zinnia elegans and Zinnia marylandica decreased as salinity increased. There are several studies that shown reducing plant heights and biomass under saline conditions [16,14,17,21,22,6,23]. There is not too much known the effects of salinity on flowering parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Yasemin (2020) [20] also presented that branch number and length of Zinnia elegans and Zinnia marylandica decreased as salinity increased. There are several studies that shown reducing plant heights and biomass under saline conditions [16,14,17,21,22,6,23]. There is not too much known the effects of salinity on flowering parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies on irrigation management of ornamental plants with lower quality water were developed by Oliveira et al (2017), Moore et al (2019), Bezerra et al (2020) and Xing et al (2021) and observed that the increase in the electrical conductivity of irrigation water reduced the growth of the ornamental species Catharanthus roseus, Allamanda cathartica, Ixora coccinea, Duranta erecta, Coleus hybridus, Acalypha wilkesiana, Ficus benjamina, Jasminium multiflorum and Plumbago auriculata. Although there are species that develop satisfactorily in saline conditions, most species are sensitive to excess salts in irrigation water, requiring studies to evaluate better management strategies (Oliveira et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This was documented by El-Fouly et al (2015) on Iris tingitana cv. Wedgewood, Oliveira et al (2017) on Catharanthus roseus, Allamanda cathartica, Ixora coccinea and Duranta erecta; in addition to Bian and Pan (2018) on Narcissus tazzeta var. chinensis, Hassan and Abd El-Azeim (2019) on Polianthes tuberosa and Hoang et al (2020) on Amaranthus tricolor.…”
Section: Introductionmentioning
confidence: 99%